Uji Kelayakan Ibu Sehati : Aplikasi Pencegahan Anemia Ibu Hamil Berbasis Android: Aplikasi Pencegahan Anemia Ibu Hamil Berbasis Android - Aurelia Rifkha Anyndie; Nurhidayat; siswati, tri (Jurnal Teknologi Kesehatan (Journal of Health Technology), 2023)
The research on the "Ibu Sehati" m-health application, conducted from January to April 2021 in Yogyakarta, aimed to assess its feasibility for providing information on anemia during pregnancy. Using the 4-D model (Define, Design, Develop, Disseminate), the study involved various stakeholders including pregnant women, health experts, and IT professionals. The application was evaluated by media and material experts, and users, achieving an average feasibility score of 89.59, classifying it as very feasible. The dissemination phase involved offline meetings with health centers and pregnant women in Sleman, DI Yogyakarta. The "Ibu Sehati" application, with its comprehensive and user-friendly features, was deemed highly suitable for its intended users.